Genome-Wide Transcriptional Responses of Mycobacterium to Antibiotics - Briffotaux, Julien; Liu, Shengyuan; Gicquel, Brigitte (Frontiers in Microbiology, 2019)
Antibiotics can stimulate or depress gene expression in bacteria. The analysis of transcriptional responses of Mycobacterium to antimycobacterial compounds has improved our understanding of the mode of action of various drug classes and the efficacy and effect of such compounds on the global metabolism of Mycobacterium. This approach can provide new insights for known antibiotics, for example those currently used for tuberculosis treatment, as well as help to identify the mode of action and predict the targets of new compounds identified by whole-cell screening assays. In addition, changes in gene expression profiles after antimycobacterial treatment can provide information about the adaptive ability of bacteria to escape the effects of antibiotics and allow monitoring of the physiology of the bacteria during treatment. Genome-wide expression profiling also makes it possible to pinpoint genes differentially expressed between drug-sensitive Mycobacterium and multidrug-resistant clinical isolates. Finally, genes involved in adaptive responses and drug tolerance could become new targets for improving the efficacy of existing antibiotics.